An Epilogue To Bilateral Investment Treaties Regime And The Fate Of Foreign Investments Protection In Indonesia - Nur Gemilang Mahardhika (Jurnal Hukum IUS QUIA IUSTUM, 2022)
Indonesia began its BITs termination movement in early 2014 by calling off the Netherlands-Indonesia BIT 1992. As of today, 29/55 of the country’s BITs that are in force have been terminated. By adopting the normative research method and utilising statutory and conceptual approaches, this paper examines two issues: first, mapping the landscape of international investment law in Indonesia in the epilogue of its long-standing BITs regime hence the probable government’s deliberations behind the action; and second, in what way would the BITs termination movement truly serve Indonesia’s national interests and benefit its economic development while promoting and protecting foreign investments – particularly on the core element of the investors’ direct right to investment arbitration. At last, the paper concludes its discussion by offering two answers: first, two lifeboats are reserved for the protection of the country’s present foreign investment, the implementation of “Sunset Cause” contained within Indonesia’s BITs as well as protectionism provisions under the country’s national investment law and other relevant regulations; and for the second, two diverged roads are laid out to choose for the protection of future foreign investments in Indonesia, the country’s Regional Trade Agreements (RTAs) containing investment provisions or its newly born model BIT which, needless to say, at least the latter must be formulated with delicate manner if the goal is to prevail Indonesia’s interests.Key Words:  Bilateral Investment Treaties; foreign investors; investor-state contracts; new model BIT; Regional Trade Agreements; sunset clauseAbstrakIndonesia memulai gerakan terminasi BIT-nya sejak awal tahun 2014 dengan membatalkan BIT Belanda-Indonesia 1992. Sampai hari ini, dari total 55 BIT negara tersebut yang masih berlaku, 29  di antaranya telah dihentikan. Dengan mengadopsi metode penelitian normatif dan menggunakan pendekatan perundang-undangan dan konseptual, tulisan ini mengkaji dua masalah: pertama, pemetaan lanskap hukum investasi internasional di Indonesia dengan berakhirnya rezim BIT yang sudah berlangsung lama juga analisa kemungkinan pertimbangan-pertimbangan pemerintah di balik tindakan tersebut; dan kedua, dengan cara apa gerakan terminasi BIT ini dapat benar-benar melayani kepentingan nasional Indonesia dan menguntungkan pembangunan ekonominya namun pada saat yang bersamaan juga mempromosikan dan melindungi investasi asing – terutama pada elemen inti yakti hak langsung investor untuk mengajukan arbitrase. Sebagai penutup, makalah ini mengakhiri diskusinya dengan menawarkan dua jawaban: pertama, dua sekoci disediakan untuk melindungi investasi asing negara saat ini, yaitu penerapan “Sunset Cause” yang terkandung dalam BIT Indonesia serta pasal-pasal pelindung dalam UU Investasi negara tersebut serta peraturan terkait lainnya; dan untuk yang kedua, dua pilihan jalan ditawarkan untuk melindungi investasi asing di Indonesia di masa depan, yaitu Regional Trade Agreement (RTA) negara tersebut yang mengandung bab investasi atau model BIT baru yang akan lahir yang, tentunya, paling tidak yang terakhir ini harus dirumuskan secara hati-hati jika tujuannya adalah untuk memenangkan kepentingan Indonesia.Kata-kata Kunci:   Bilateral Investment Treaty; investor asing; perjanjian investor-negara; model BIT baru; Regional Trade Agreement; Sunset Clause